PENGARUH PUPUK DAN AMELIORAN PADA TANAMAN PAKCOY BUDIDAYA SISTEM VERTIKULTUR DENGAN FERTIGASI SUMBU DI LAHAN KERING - Ana Anggelina Juliana Kolo; Tobing, Wilda Lumban; Azor Yulianus Tefa; Natalia Desy Djata Ndua (Prodi Agroteknologi Fakultas Agro Teknologi Universitas Prima Indonesia, 2024)
The purpose of this study was to determine the effect of N fertilizer and ameliorant types on the growth, yield, and nitrogen absorption of pak choy (Brassica rapa L.) plants through wick fertigation systems in vertical cultivation in dry land. The research method used a split-plot design. The main plot is N fertilizer consisting of BPN + Urea, BPN + POC, and BPN + Urea + POC. The subplots are ameliorant types consisting of soil, soil: biochar (1:1), and soil: compost (1:1), which were repeated 3 times so that 27 total experimental combinations were obtained. The results showed that there was an interaction between N fertilizer and ameliorant types that could increase the growth and production of pak choy plants, where the interaction of BPN + Urea + POC treatment with ameliorant types of soil: biochar (1:1) gave the best results in observing the stem diameter and root length of pak choy plants. N fertilizer was able to increase the growth and production of pak choy plants, where BPN + POC gave the best results in observing the dry weight of the crown and N absorption of pak choy plants. The type of ameliorant is able to increase the growth and production of pak choi plants where the soil:compost (1:1) treatment gives the best results in observing plant height and the number of pak choi leaves.